Multi-stress radioactive-tolerant Exiguobacterium acetylicum CR1 and its applicability to environmental cesium uptake bioremediation. (20th December 2018) - Oh, Seo Yeong; Heo, Nam Su; Shukla, Shruti; Kang, Sung-Min; Lee, Ilsong; Lee, Hoomin; Bajpai, Vivek K.; Jang, Sung-Chan; Han, Young-Kyu; Roh, Changhyun; Huh, Yun Suk
Abstract: Several industries using gamma sterilization techniques for food safety, and long shelf-life purposes. Nuclear energy production has increased the amount of spent nuclear fuel produced, which poses risks of severe diseases in human. Cesium is one of the most hazardous material can cause human exposure to air, water, and food. The efficient removal of cesium ions (Cs + ) has been emphasized using biological control strategies. In this study, we isolated a new Cs + -tolerant (100, 500, and 750 ppm) and gamma radiation resistant (1, 3, and 5 kGy) soil bacterium (CR1) from the soil around a nuclear power plant in Korea, which was identified as Exiguobacterium acetylicum CR1 by 16S rRNA sequencing. E. acetylicum CR1 was found to be resistant to high doses of gamma radiation without any loss in Cs + tolerance or survival. Furthermore, E. acetylicum CR1 was found to act as a microbiological control agent with respect to the removal of cesium from contaminated water. Interestingly, after gamma radiation exposure, E. acetylicum CR1 developed significantly ( p < 0.05) greater Cs + bio-sorption capacity than non-irradiated control cells (24.63 ± 0.02% vs. 12.54 ± 0.06%), which confirmed that gamma radiation had no negative impact on its ability to remove Cs + or on its growth/survival. The ability of E. acetylicum CR1 to adsorb Cs + from contaminated water samples or radioactive environmental waste suggests it has broad spectrum potential as an environmentally friendly remedial tool in the contexts of soil ecology, agriculture, crop management, food, and medicine. Graphical abstract: Highlights: Radio-tolerant E. acetylicum CR1 was isolated from nuclear power plant effluent. E. acetylicum CR1 showed significant cesium (Cs + )-tolerance ability. E. acetylicum CR1 also exhibited extended gamma radiation resistance. E. acetylicum CR1 significantly removed Cs + radionuclides from environmental sample. E. acetylicum CR1 has ability for the bioremediation of radionuclides.